A qualitative analysis of study participant and study partner experiences with the consent process: Assessments guiding the development of an electronic consent (ECONSENT): Dementia care research (research projects; nonpharmacological) / Use of technologies. (7th December 2020) - Chin, Erin; Croes, Kenneth; Dykema, Jennifer; Suver, Christine; Hamann, Jennifer; Truong, Amy; Doerr, Megan; Lah, James J; Goldstein, Felicia C; Blazel, Hanna; Manzanares, Cecelia; Edwards, Dorothy Farrar
Abstract: Background: The informed consent process educates potential participants about a research study and guides them to make a decision about participation. Most important, the consent document should meet the needs of the participant so they can make an educated decision. Studies have shown consent documents can be lengthy, redundant and ineffective at enhancing comprehension. We examined the traditional consent process from the perspective of research participants, including people commonly underrepresented in research, and from study partners from the University of Wisconsin‐Madison and Emory University Alzheimer's Disease Research Centers. Method: Private interviews were conducted with 15 participants and 8 participant/study partner dyads. The interviews were voluntary and the interviewer was not the same person who consented the participants to avoid any bias or influence over the participant's response. Each person was asked a series of questions about their overall experience with the informed consent process. In order to evoke prior observations, respondents were encouraged to review the consent form throughout the interview. Responses were recorded, transcribed and coded. Result: Analysis of the interviews revealed participants were overall satisfied with the consent process. Well‐trained study coordinators made a notable difference in the consent experience. Reported shortcomings highlighted by study partners include the length of the consent form and complex language. Some people felt that both the length and complexity were excessive based on the risks and benefits of participation. Others felt a better explanation was needed to explain more complex procedures and concepts, with one pointing out, "The DNA might pose a little problem for people…depending on how far along the person is with their understanding of medical stuff." Some recommended using videos or online chats to make it easier for people to understand. Conclusion: When designing an update for a process as vital as the consent it is imperative to capture the perspective and needs of those it directly affects. Participants and study partners offered recommendations, providing a starting point in the development of an eConsent version. In exploring an electronic approach, we hope to improve comprehension by allowing participants to have control over the order and level of detail of information presented to them.